2015
DOI: 10.5005/jp-journals-10024-1745
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ocimum sanctum on Oral Cancer Cell Line: An in vitro Study

Abstract: Background: Cancer till today remains the leading cause of death in both developed and developing countries. Plants have been beacon of therapeutic sources for curing diseases from times immemorial. Hence, the present study aimed at evaluating the antiproliferative activity of extract of Ocimum sanctum leaves on oral cancer cell line. Objectives:• Clinical significance: Ocimum sanctum herb which is abundantly grown in India can be used for its anticancer properties for treating oral cancer. This will not only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 9 publications
1
5
0
Order By: Relevance
“…In addition, fluorescent staining with Hoechst 33258 showed increased and consistent nuclear condensation and shrinkage, cell growth inhibition and apoptotic body formation in EO treated colon cancer cells in comparison to control cells that showed rounded intact nuclei. Similar findings on the Ocimum viride essential oil were also reported by Sharma and coworkers against COLO 205 cells (Sharma et al, 2016), other species from Ocimum genus such as Ocimum basilium showed in vitro cytotoxicity against cancer cells (Zarlaha et al, 2014), Ocimum sanctum showed to trigger cell death by apoptosis against human breast, liver and oral cancer cells etc (Manaharan et al, 2016;Sharma et al, 2016;Shivpuje et al, 2015). Molecular docking analysis was performed to confirm the binding efficacy of thymol from essential oil to Beclin protein that functions in autophagy, it interacts with class III PI3K complex components and Bcl-2 and lysosomal degradation pathway (Domínguez-Martín et al, 2018;Kim et al, 2017;Li et al, 2017).…”
Section: Discussionsupporting
confidence: 71%
“…In addition, fluorescent staining with Hoechst 33258 showed increased and consistent nuclear condensation and shrinkage, cell growth inhibition and apoptotic body formation in EO treated colon cancer cells in comparison to control cells that showed rounded intact nuclei. Similar findings on the Ocimum viride essential oil were also reported by Sharma and coworkers against COLO 205 cells (Sharma et al, 2016), other species from Ocimum genus such as Ocimum basilium showed in vitro cytotoxicity against cancer cells (Zarlaha et al, 2014), Ocimum sanctum showed to trigger cell death by apoptosis against human breast, liver and oral cancer cells etc (Manaharan et al, 2016;Sharma et al, 2016;Shivpuje et al, 2015). Molecular docking analysis was performed to confirm the binding efficacy of thymol from essential oil to Beclin protein that functions in autophagy, it interacts with class III PI3K complex components and Bcl-2 and lysosomal degradation pathway (Domínguez-Martín et al, 2018;Kim et al, 2017;Li et al, 2017).…”
Section: Discussionsupporting
confidence: 71%
“…13 Correspondingly in our study canagliflozin and dapagliflozin also have shown significant loss of cell viability in oral squamous cell carcinoma KB cell lines at concentrations of 250µg/ml and 400µg/ml in comparison with standard drug 5-fluorouracil, also we have detected the cells underwent reduction and decline in number exhibiting positive cytotoxic activity and the probable mechanism would be because of the restriction of glucose uptake and curbing Mitochondrial intracellular ATP synthesis thereby limiting the cell cycle of cancer cells. 21 In present study canagliflozin was more cytotoxic than dapagliflozin in KB cell line as established by IC50 values.…”
Section: Discussionmentioning
confidence: 49%
“…The induction of intrinsic and extrinsic apoptotic pathways by B. serrata extract and boswellic acids has also been demonstrated (29). Numerous plant extracts have been shown to have the ability to stop cancer cells from proliferating, making them useful in the treatment of cancer (27,30). According to Huang et al, a B. serrata extract containing β boswellic acids and related compounds prevents mice from developing tumours when induces tumour growth by preventing the up-regulation of pro-inflammatory cytokine proteins.…”
Section: Resultsmentioning
confidence: 99%